Septoplasty and septoplasty with inferior turbinoplasty in the management of nasal septal deviation with inferior turbinate hypertrophy - Rajashekhar, K.; Parameshwar, K.; P. Goud, K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasal obstruction is a highly prevalent problem caused by nasal septal deviation, with or without inferior turbinate hypertrophy. Nasal septoplasty and inferior turbinoplasty can improve the nasal airways. This study was designed to assess the efficacy of septoplasty alone and septoplasty with inferior turbinoplasty in cases having nasal septal deviation with inferior turbinate hypertrophy. Methods: A total 70 cases clinically diagnosed with the deviated nasal septum and inferior turbinate hypertrophy were randomly divided into two groups. Group 1 cases were under septoplasty alone and group 2 cases were under septoplasty with inferior turbinoplasty. Symptom improvement scores was assessed by sino nasal outcome test-20 (SNOT-20). Results: The mean reduction symptom score of nasal obstruction was 1.73 in septoplasty with inferior turbinoplasty group, while in septoplasty group it was 1.06. The mean reduction symptom score in group 2 was statistically significant. All the cases of group 2 had adequate first pass diagnostic nasal endoscopy (DNE). While in group 1, majority cases had inadequate first pass DNE. Conclusions: First pass DNE findings were favourable in the cases under septoplasty with inferior turbinoplasty Septoplasty with inferior turbinoplasty is effective in the reduction of nasal obstruction, facial pain, sleep difficulty, decrease in attentiveness and irritability in cases having deviated nasal septum with inferior turbinate hypertrophy.